Lubricity effectiveness of bio-lubricant modified with multi-wall carbon nanotube and organic polymer - Opia, Anthony Chukwunonso; Abdollah, Mohd Fadzli; Chinedu Mamah, Stanley Chinedu; Abdul Hamid, Mohd Kameil; Syahrullail, Samion; Ibrahim, Audu Ali; Johnson, Charles; Basiron, Juliana; Basiron, Juliana (Elsevier, 2023)
The development of effective bio lubricants with anti-friction and wear properties is gaining recognition due to their ecofriendly nature and good lubrications in mitigating challenges associated with friction and wear on tribo-components during lubrication. In this research, rapeseed oil served as the base lubricant, and the high frequency reciprocating rig was utilized to examine the responsiveness of the multiwall carbon nanotubes (MWCNTs) and Eichhornia crassipes carboxylmethyl cellulose (EC-CMC) polymer additives. To determine the constituents and strength of the formulations, the samples were characterized using scanning electron microscope, Energy-dispersive X-ray, Fourier transform infrared spectroscopy, Raman, and X-ray photoelectron spectroscopy. The tribological test was conducted in terms of synergistic tendency, load carrying capacity, friction and wear reduction as well as tribo-film nature. The investigation came to the following conclusions: Depending on the operating conditions, all nanoparticle suspensions showed decreases in friction and wear relative to the base oil; MWCNTs yielded better wear reduction performance while EC-CMC demonstrated outstanding friction reduction operations compared to based lubricant; the suspensions with 0.8% MWCNTs +0.5% EC-CMC had the best tribological behavior, exhibiting high percentage reduction on friction (67.8%) and wear (37.9%) with low levels on the surface roughness. Using XPS analysis, the detection of additive elements and tribo-films on the wear surfaces was validated, and their nature was analyzed in the context of the related tribo-chemistry findings. The study concluded that effective friction reduction during testing is a result of the additive’s rapid penetration into the interface region and its nanosized structure.